The Influence of Self-Discipline and Peer Environment on the Academic Achievement of Junior High School Students in Sepaku District - Khalim, Muhammad Zainul; Widiyanah, Ima; Sholeh, Muhamad; Khamidi, Amrozi (Universitas Pahlawan Tuanku Tambusai, 2026)
The aim of this study is to empirically analyze the influence of self-discipline and peer environment on the academic achievement of junior high school students in Sepaku District, both partially and simultaneously, within the framework of integrating internal and external factors of adolescent development. A quantitative approach with an explanatory research design was used to test the influence of self-discipline and peer environment on students’ academic achievement through inferential statistical analysis. The study population consisted of 1,125 students, with a sample of 137 students determined using the Slovin formula at an 8% error rate. Data were collected through questionnaires, documentation, and observation, and then analyzed using descriptive and inferential statistics. The results indicate that self-discipline has a positive and significant effect on the academic achievement of junior high school students in Sepaku District. Students’ ability to manage time, obey rules, and maintain consistency in learning plays an important role in improving academic performance. Conversely, the peer environment has a negative and significant effect, indicating that less supportive social interactions can reduce students’ focus, commitment, and learning outcomes. Simultaneously, these two variables contribute 52.0% to the variation in academic achievement, suggesting that learning success is influenced by the synergy of internal and external factors.